Sistem Informasi Penjualan Sembako Pada Toko Srimukti Pasar Serang Kecamatan Serang Baru Berbasis Android - Muhamad Fatchan (Teknik Informatika, Universitas Pelita Bangsa, 2020)
Grocery store is one of the businesses engaged in the economy, which is currently still using a conventional system. In this research, the problem that often occurs about how to implement android-based groceries sales is formulated so that promotions and groceries sales transactions at Srimukti Stores become more secure and accurate. While the purpose of this research is to design an interface, the sales system uses PHP, the database uses MYSQL and the software uses Android Studio. The data obtained is then analyzed and illustrated using the object-oriented waterfall method such as UML (Unified Modeling Language). The result of making this application is that with the android-based basic food sales system the customer does not need to come to the store, customers can directly input and check stock information and prices of updated goods via an android smartphone, by opening the Srimukti Toko basic food sales application and then selecting the main menu for input ordering . The sale of basic food at Srimukti Shop makes it easy for the admin as the shop owner or customer to find out the price of the update.. Keywords : Information Systems, Waterfall Methods, PHP, MySQL.